2019
DOI: 10.1002/ange.201907298
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Reversible Single Molecule Electrochemistry of Alexa Fluor 647 Dyes by Total Internal Reflection Fluorescence Microscopy

Abstract: Alexa Fluor 647 is aw idely used fluorescent probe for cell bioimaging and super-resolution microscopy. Herein, the reversible fluorescence switching of Alexa Fluor 647 conjugated to bovine serum albumin (BSA) and adsorbed onto indium tin oxide (ITO) electrodes under electrochemical potential control at the level of single protein molecules is reported. The modulation of the fluorescence as af unction of potential was observed using total internal reflectance fluorescence (TIRF) microscopy. The fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…[1][2][3] While a variety of spectroscopic-based methods have played a central role in understanding reaction kinetics and mechanisms, these techniques often produce ensemble information that contains a collection of process and molecule averages. [4][5][6] Noteworthily, singlemolecule imaging methods can provide a unique advantage of in situ reaction monitoring, revealing individual pathways of different molecules, and elucidating important knowledge about system heterogeneities which might be difficult to obtain from using spectroscopic techniques. [6][7][8][9] Single-molecule fluorescence (smFL) imaging, particularly, received significant interest due to its high spatial resolution, noninvasive sample preparation, and characterization, as well as broad applicability to a wide variety of systems, including but not limited to, catalysis, [10][11][12] electrochemistry, [13][14][15] and interfacial science.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While a variety of spectroscopic-based methods have played a central role in understanding reaction kinetics and mechanisms, these techniques often produce ensemble information that contains a collection of process and molecule averages. [4][5][6] Noteworthily, singlemolecule imaging methods can provide a unique advantage of in situ reaction monitoring, revealing individual pathways of different molecules, and elucidating important knowledge about system heterogeneities which might be difficult to obtain from using spectroscopic techniques. [6][7][8][9] Single-molecule fluorescence (smFL) imaging, particularly, received significant interest due to its high spatial resolution, noninvasive sample preparation, and characterization, as well as broad applicability to a wide variety of systems, including but not limited to, catalysis, [10][11][12] electrochemistry, [13][14][15] and interfacial science.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule biosensing requires not only the instrumental sensitivity to measure signal from single analytes, but the analytical sensitivity of high-affinity biomolecular interactions, thoughtful assay design, and replicate measurements to account for the significant sampling variability that occurs in experiments at the single-molecule level (Battich et al, 2013;Zhang et al, 2014). Several single-molecule biosensors have been reported using a variety of sensing modalities, including electrochemical sensing, plasmonic sensing, interferometry, and fluorescence spectroscopy and microscopy (Huang et al, 2008;Zevenbergen et al, 2011;Baaske et al, 2014;Assad et al, 2017;Cohen and Walt, 2017;Landry et al, 2017;Mauranyapin et al, 2017;Fan et al, 2019;Akkilic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The inspiration for exploring electrochemical switching came from the previous research that the fluorescence of some fluorophores can be altered by external electrical potential. [19][20][21] Our recent study showed that the fluorescence intensity of Alexa Fluor 647 (Alexa 647) could be modulated by the electrochemical potential (Supplementary Figure 1-3, Supplementary Movie 1) 22 . However, in previous research [19][20][21][22] only the brightness of the fluorophore can be tuned using electrochemical potential, the stochastic switching of the molecules between their ON and OFF states as required for STORM imaging was not achieved.…”
mentioning
confidence: 99%
“…[19][20][21] Our recent study showed that the fluorescence intensity of Alexa Fluor 647 (Alexa 647) could be modulated by the electrochemical potential (Supplementary Figure 1-3, Supplementary Movie 1) 22 . However, in previous research [19][20][21][22] only the brightness of the fluorophore can be tuned using electrochemical potential, the stochastic switching of the molecules between their ON and OFF states as required for STORM imaging was not achieved. To understand why electrochemical switching of fluorophores might be possible requires an understanding of how the fluorophores can be photochemically switched between the ON and OFF states.…”
mentioning
confidence: 99%
See 1 more Smart Citation